Subthalamic Nucleus Degeneration As A Dark Cause of Parkinson’s Disease Due to Subarachnoid Hemorrhage: A Preliminary Experimental Study - Mehmet Hakan Şahin; Mete Zeynal (Journal of Contemporary Medicine, 2023)
Background: Although the subtahalamic nucleus degeneration has been accused of Parkinson’s disease, the obscure roles of subtalamic nucleus degeneration induced by subarachnoid hemorrhages has not been adequately studied. The aim of the study is to examine the histopathological changes in the subthalamic nucleus after subarachnoid hemorrhage. Materials and Methods: Twenty-one wild male healthy rabbits were included in this study. The test subjects were divided as: control (GI, n=5); SHAM 1.2 cc of saline injected (GII, n=6) and 1.2 cc of autologous blood injection into cisterna magna (GIII, n=10). They followed up for three weeks and sacrificed under general anesthesia. Vasospasm index (VSI) was estimated by the circle surface estimation method, degenerated neuron densities of the subthalamic nucleus were estimated by Stereological methods and analyzed by Mann Witney U test. Results: Two rabbits dead in the study group were represented by meningeal irritation signs and unconsciousness. Prolonged QT intervals, ST depressions, and low voltage QRSs were noticed in GIII animals. Numerical documents of heart-respiratory rates (n/min), VSI values, and degenerated neuron densities of the subthalamic nucleus (n/mm3) as follows: 1.05±0.03/ 219±324/21±4/8±3 in GI; 1.75±0.23/209±14/15±4/16±4 in GII; and 2.03±0.14/175±19/19±5/123±21 GIII. P values between the VSI values and degenerated neuron densities of the subthalamic nucleus were nearly eqund: p